Evaluasi dan penatalaksanaan pasien medically-compromised di tempat praktek gigi Evaluation and management of medically compromised patient in dental practice - Evy Eida Vitria (Journal of Dentomaxillofacial Science, 2011)
As a dentist, before doing dental procedure, especially regarding surgical intervention, It is necessary to ascertainthe general health of the patient whether the condition is safe enough to do dental procedure. This requires anappropriate and accurate evaluation in determining the systemic condition of medically compromised patients,which focus on pathophysiology of the disease, signs and symptoms, laboratory findings, currently accepted medicaltherapies, as well as recommendations for specific dental treatment. So, the best possible treatment procedures canbe provided and complications can be avoided.